Teacher training, primary education and educational quality in Angola: gaps and bridges in the relationship (Revista Internacional de Formação de Professores, 2020)
This paper presents reflection on bridges and gaps in the relationship between teacher trainingprocesses and the development of the primary education curriculum in Angola. From a dialectical-reflexive andcritical perspective, we discuss the need for teacher training that can be combined with the educational context ofcontemporary. Thus, this study questioned the problematic and complex relationship between the curriculardesign of teacher education and the development of the primary education curriculum in Angola, which require aperspective of globalization and contextualization of training, using new technologies, able to guarantee the educational quality in Angola
Keywords: Teacher training. Primary school. Quality of teaching